2011
DOI: 10.1128/aac.01014-10
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Action of Polyphosphate on Porphyromonas gingivalis

Abstract: Polyphosphate [poly(P)] has antibacterial activity against various Gram-positive bacteria. In contrast, Gram-negative bacteria are generally resistant to poly(P). Here, we describe the antibacterial characterization of poly(P) against a Gram-negative periodontopathogen, Porphyromonas gingivalis. The MICs of pyrophosphate (Na 4 P 2 O 7 ) and all poly(P) (Na n ؉ 2 P n O 3n ؉ 1 ; n ‫؍‬ 3 to 75) tested for the bacterium by the agar dilution method were 0.24% and 0.06%, respectively. Orthophosphate (Na 2 HPO 4 ) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
(45 reference statements)
6
39
1
Order By: Relevance
“…Recently, however, polyP was demonstrated to be bactericidal against Porphyromonas gingivalis, a black-pigmented anaerobic Gram-negative rod associated with periodontal disease (31). The MICs of polyP with different linear phosphorus chain lengths (3 to 75) for the bacterium were 0.06%, which is much lower than the MICs previously reported for Gram-positive bacteria (31).…”
contrasting
confidence: 39%
See 3 more Smart Citations
“…Recently, however, polyP was demonstrated to be bactericidal against Porphyromonas gingivalis, a black-pigmented anaerobic Gram-negative rod associated with periodontal disease (31). The MICs of polyP with different linear phosphorus chain lengths (3 to 75) for the bacterium were 0.06%, which is much lower than the MICs previously reported for Gram-positive bacteria (31).…”
contrasting
confidence: 39%
“…The MICs of polyP with different linear phosphorus chain lengths (3 to 75) for the bacterium were 0.06%, which is much lower than the MICs previously reported for Gram-positive bacteria (31). Nota-bly, there is ample evidence to show that the mode of bactericidal action of polyP against Gram-negative bacteria is different from that against Gram-positive bacteria: antibacterial activity of polyP against P. gingivalis was independent of the bacterial growth phase, and no P. gingivalis cells with obviously aseptate and elongated morphology were observed when the bacterial cells were exposed to polyP (31).…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…These differentially expressed genes or proteins were linked to bacterial invasion, iron transport, and an oxidative-stress response. A recent study showed that inorganic polyphosphates (potential antibacterial agents) inhibited energydriven uptake of hemin by P. gingivalis and repressed the expression of oxidative stress-induced proteins, including superoxide dismutase (SOD) (15), which provides indirect evidence linking hemin to SOD expression. To better understand the response of P. gingivalis to hemin-limited conditions and the association between iron/hemin concentrations and oxidative stress, we investigated the expression and activity of OxyR in P. gingivalis under hemin-limited as well as excess-hemin conditions.…”
mentioning
confidence: 99%